Analysis of face stability for shallow shield tunnels in sand - Qiang, Sihan; Zhao, Lizhi; Wang, Xuehai; Li, Xiaoming; Wang, Fengnian (Frontiers in Earth Science, 2023)
The stability of the tunnel face is the key problem in shield tunnel construction. This paper focuses on the face stability of a shallow tunnel in sand. Numerical simulation and theoretical analysis are combined to study the limit support pressure and failure zone. Firstly, numerical simulation is employed to study the collapse of the tunnel face, obtaining the limit support pressure and collapse zone. A new failure model suitable for shallow tunnels is constructed based on these numerical simulations. Then, an analytic solution for the limit support pressure is derived using limit analysis upper bound theory. The accuracy and applicability of this proposed model are verified by comparing it with numerical results and classical analytical models. Through this research, it is found that the proposed model provides a more accurate description of situations where soil arches cannot be formed for shallow tunnels in sand, leading to higher accuracy in calculating the limit support pressure. The influence of various factors on stability of the tunnel face is analyzed, revealing mechanisms of tunnel face collapse.